2016
DOI: 10.1111/anu.12362
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary methionine concentrations on growth performance of juvenile Nile tilapia (Oreochromis niloticus) fed diets with two different digestible energy levels

Abstract: A growth trial was conducted to examine the effect of dietary digestible energy (DE) content on methionine (Met) utilization and requirement in juvenile Nile tilapia (Oreochromis niloticus). Ten iso‐nitrogenous (288 g kg−1 protein) practical diets, with two DE levels (10.9 MJ kg−1; 12.4 MJ kg−1) and five methionine supplementation levels (0, 1, 2, 4 and 6 g kg−1), were hand‐fed twice daily to triplicate groups of Nile tilapia (initial body weight 8.95 ± 0.06 g) for 8 weeks. Weight gain (WG) and specific growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…He et al (2017) and Diogenes et al (2016) estimated the dietary methionine requirement of Nile tilapia at 9.9 g/kg of diet, which is close to the estimated value (9.2 g/kg) in the AA balanced diet. Similarly, Bomfim et al (2008) estimated the optimum dietary methionine requirement to be 9.1 g/kg of diet for optimum growth of Nile tilapia.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…He et al (2017) and Diogenes et al (2016) estimated the dietary methionine requirement of Nile tilapia at 9.9 g/kg of diet, which is close to the estimated value (9.2 g/kg) in the AA balanced diet. Similarly, Bomfim et al (2008) estimated the optimum dietary methionine requirement to be 9.1 g/kg of diet for optimum growth of Nile tilapia.…”
Section: Discussionsupporting
confidence: 52%
“…The Nile tilapia is cultured under diverse rearing conditions in many countries due to its high growth rate and yield. Through the years, numerous studies have been carried out to estimate essential amino acid (EAA) requirements of Nile tilapia to attain maximum growth rate and feed utilization (Nguyen et al, 2019; Zaminhan et al, 2017, 2018; Diogenes et al, 2016; Figueiredo‐Silva, Lemme, Sangsue, & Kiriratnikom, 2015; Gan et al, 2016; He et al, 2017; Michelato et al, 2016, 2017; Yue et al, 2014; Santiago & Lovell, 1988). Nile tilapia has been genetically improved over 15 generations of selection with 10% improvement in weight gain per generation (Eknath & Hulata, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The crude lipids in the carcasses were significantly different ( p < .05) at the final time between DPI 1.0 (presented a low level 8.7%) and the remaining treatments. High levels of ash (24.7%) and protein (60.6%) were obtained, even though the values of crude lipids for weeks 17 and 34 (DPI 1.4, DRI 1.2) were high compared with those determined by Michelato et al (), who found 6.7%–3.8% (chloroform: methanol extraction) in a tilapia culture with supplementation of methionine and taurine; levels of 5.7%–10.7% were found in 80.1–90.3 g fish that were supplemented with methionine (He et al, ). The high values in the carcasses could have been affected by the protein in the feed (40% protein during all culture times).…”
Section: Discussionmentioning
confidence: 61%
“…With all these results, we established a base for using the DPI metric to feed in high density RASs in warm climates and in cultures with temperatures above 30°C. Azim and Little, (2008) Michelato et al (2018), who found 6.7%-3.8% (chloroform: methanol extraction) in a tilapia culture with supplementation of methionine and taurine; levels of 5.7%-10.7% were found in 80.1-90.3 g fish that were supplemented with methionine (He et al, 2016). The high values in the carcasses could have been affected by the protein in the feed (40% protein during all culture times).…”
Section: Initial Biomass (G) Final Weight (G) Final Biomass (G)mentioning
confidence: 99%
“…The SGR values may vary depending on the experimental conditions of each study. For fast-growing fish like the Nile tilapia, the present SGR ranged from 2.27 to 5.56% day -1 (Figueiredo-Silva et al, 2015;He et al, 2017;He et al, 2020). Fast-growing species allocate a greater fraction of their amino acid requirements for body protein deposition, and consequently, have greater efficiency of utilization of amino acids (Helland;Hatlen;Grisdale-Helland, 2010;He et al, 2013;Hua;Suwendi;Bureau, 2019).…”
Section: Resultsmentioning
confidence: 94%